ANALYSIS OF THE EFFECT OF POPULATION DEVELOPMENT, PERCAPITA EXPENDITURE AND OPENUNEMPLOYMENT RATE ON THE POOR POPULATION IN ACEH PROVINCE 2000-2019 - Fajar Meutia; Ulfa Mahira; Husnul Khatimah; Murtala; Mutia Rahmah (International Conference on Health Science, Green Economics, Educational Review and Technology, 2020)
This study examined the relationship between population density, per capita expenditure, open unemployment rate, and the poor people in Aceh province. This study used secondary data from 2000 to 2019. The data were analyzed using the Vector Autoregression (VAR) analysis method with the help of Eviews 10. The results indicated that population density had no positive and significant effect on the poor people, per capita expenditure had a positive but insignificant effect on the poor people, and the open unemployment rate had a positive and significant effect on the poor people.